2020
DOI: 10.1093/mnras/staa1731
|View full text |Cite
|
Sign up to set email alerts
|

The influence of angular momentum and environment on the H i gas of late-type galaxies

Abstract: We use high-resolution H i data from the Westerbork H i Survey of Spiral and Irregular Galaxies (WHISP) to study the H i and angular momentum properties of a sample of 114 late-type galaxies. We explore the specific baryonic angular momentum–baryonic mass (jb–Mb) relation, and find that an unbroken power law of the form $j_\mathrm{ b} \propto M_\mathrm{ b}^{0.55 \pm 0.02}$ fits the data well, with an intrinsic scatter of ∼0.13 ± 0.01 dex. We revisit the relation between the atomic gas fraction, fatm, and the i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 87 publications
5
31
0
Order By: Relevance
“…The fact that the slope of the relation is 0.5−0.6 is remarkable as this value is very close to the slope of the relation of dark matter haloes, j h ∝ M 2/3 h (e.g. Fall 1983;Romanowsky & Fall 2012;Obreschkow & Glazebrook 2014;P18 and references therein) While these studies have built a relatively coherent picture of the stellar component, the gas ( j gas − M gas ) and baryonic ( j bar − M bar ) relations remain somewhat less well explored, although studies performed in recent years have started to delve into this (Obreschkow & Glazebrook 2014;Butler et al 2017;Chowdhury & Chengalur 2017;Elson 2017;Kurapati et al 2018;Lutz et al 2018;Murugeshan et al 2020). In fact, different authors have reported different results regarding the nature of the j bar − M bar relation, such as whether or not the slope of the correlations in the j bar − M bar and j * − M * planes are the same, if dwarf galaxies follow a different sequence than higher-mass spirals, or whether or not the relations have a break at a characteristic mass.…”
Section: Introductionsupporting
confidence: 55%
See 3 more Smart Citations
“…The fact that the slope of the relation is 0.5−0.6 is remarkable as this value is very close to the slope of the relation of dark matter haloes, j h ∝ M 2/3 h (e.g. Fall 1983;Romanowsky & Fall 2012;Obreschkow & Glazebrook 2014;P18 and references therein) While these studies have built a relatively coherent picture of the stellar component, the gas ( j gas − M gas ) and baryonic ( j bar − M bar ) relations remain somewhat less well explored, although studies performed in recent years have started to delve into this (Obreschkow & Glazebrook 2014;Butler et al 2017;Chowdhury & Chengalur 2017;Elson 2017;Kurapati et al 2018;Lutz et al 2018;Murugeshan et al 2020). In fact, different authors have reported different results regarding the nature of the j bar − M bar relation, such as whether or not the slope of the correlations in the j bar − M bar and j * − M * planes are the same, if dwarf galaxies follow a different sequence than higher-mass spirals, or whether or not the relations have a break at a characteristic mass.…”
Section: Introductionsupporting
confidence: 55%
“…For instance, our mass coverage at M bar < 10 9 M is a bit more complete (11 galaxies in their work vs 23 in our convergent sample), and, very importantly, we applied a converge criterion to all our sample in order to select only the most accurate j profiles. In addition to this, while both studies use near infrared luminosities to trace M * (mostly 3.6µm in our case, and 2.2µm for Murugeshan et al 2020), we use a Υ that has been found to reduce the scatter in scaling relations that depend on M * such as the baryonic Tully-Fisher relation (see Lelli et al 2016b), while the calibration used by Murugeshan et al (2020) may have a larger scatter, up to one order of magnitude in M * at given infrared luminosity (Wen et al 2013). Finally, we determine V * instead of assuming co-rotation of gas and stars, although this does not play an important role when determining the global j bar − M bar relation (cf.…”
Section: J Bar − M Bar Relationmentioning
confidence: 99%
See 2 more Smart Citations
“…To incorporate f gas , we rewrote the above expression (using 4 We note that assuming a non-constant σ gas is not enough to alleviate the mentioned discrepancies. To match our relations, σ gas ∝ M ∼0.25 bar is required; however, it is observed that σ gas ∝ M 0.07 bar (e.g., Murugeshan et al 2020). Assuming a constantσ gas , as in Romeo (2020), this relation predicts j gas ∝ M bar at fixed f gas and j gas ∝ f gas at fixed M bar .…”
Section: Disc Instabilitymentioning
confidence: 69%